Technical feasibility study on jackfruit seed flour substitution in miki production - Serate , Matthew Benjamin Alcantara (1995.)
Jackfruit seed (Artocarpus heterophyllus) was made ito flour and added to wheat flour in miki production using four different jackfruit seed (JSF) flour to wheat flour (WF) ratios : 0/100 (sample A), 10/90 (sample B), 20/80 (sample C), and 30/70 (sample D).
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Artocarpus heterophyllus